Spawning behaviour of Arctic charr (Salvelinus alpinus) : risk of sperm competition and timing of milt release for sneaker and dominant males - Sørum, Vidar; Figenschou, Lars; Rudolfsen, Geir; Folstad, Ivar (Behaviour, 2011)
A mismatch in timing between the release of male and female gametes in external fertilizers may lead to failed fertilization or, under sperm competition, reduced paternity. To quantify the actual synchrony of gamete release and the level of sperm competition we placed video cameras on two spawning grounds of a naturally spawning population of Arctic charr ( Salvelinus alpinus). Females release eggs in response to courting (quivering) in less than 1% of the cases, yet to both dominant and sneaker males. That is, females initiated spawning with dominant males in 73.3% of the recorded spawning events. Although the actual spawning seems to be largely under female control, 55.6% of spawning events occur under sperm competition. The average time delay between dominant and sneaker males milt release under sperm competition is 0.68 s. Thus, female reproductive decisions seem to be strongly influenced by male-male competition and this may have set the stage for the evolution and maintenance of the observed plasticity in ejaculate characteristics of male charr.